The Match-Up Hypothesis Revisited: A Social Psychological Perspective - (:unkn) unknown (USC ANNENBERG PRESS, 2017)
Drawing on the social psychology literature, two studies are presented that examine the role of self-esteem and body-esteem in driving the effect of using highly attractive female imagery in ads targeting women. In two 2 x 2 experiments, model physical attractiveness and product category are manipulated. The results indicate that (1) while highly attractive female models perform better in the ads of attractiveness-related products, moderately attractive female models work better in the ads of non-attractiveness-related products and (2) self-esteem and body esteem play a significant role on how female imagery in ads relate to advertising effectiveness. We found rather consistent yet statistically insignificant evidence for the proposition that low self-and body esteem amplifies the reversal effect predicted by the match-up hypothesis.
Keywords: the match-up hypothesis; women; self-esteem; body esteem; advertising effectiveness; PHYSICAL ATTRACTIVENESS; BRAND ATTITUDE; SELF-ESTEEM; CELEBRITY ENDORSER; PRODUCT TYPE; BEAUTY; MODELS; PERSONALITY; IMPACT; SPOKESPERSON